Pipe Dreams: Israel and Iran as Euro-American Projects - Ram, Haggai (جماعة, 2006)
This short essay sheds new light on the special relationship between Israel and Iran under the Shah’s regime, and provides an unconventional approach to the study of the Israeli discourse on the ‘Iranian threat’ after the 1979 Iranian revolution. The author draws attention to the reciprocal images of Iran and Israel before the revolution. He argues that these images enabled the two states to envision each other as analogous Euro-American, secular enclaves in the Arab-Muslim Orient. It is within the context of these imagined affinities that the Israeli discourse on Iran after the revolution, and its expulsion to the realm of radical alterity in Israeli collective imaginary, should be evaluated. Hegemonic conceptions of Iran are driven by hegemonic concerns over the nature of Israeli identity, and by processes taking place within Israeli society, no less than by a strategic rivalry between the two states.